Corporate governance and firm performance : a two-country comparison of government-linked companies. - Lim, Aaron Jun Ming. (2008)
In this study, we first compare the performance and valuation of government-linked companies (GLCs) in Singapore and Malaysia under the respective government holding companies, Temasek Holdings and Khazanah Nasional Berhad. We subsequently use government ownership and corporate governance variables to explain the differences.